Comparative Analysis of Acceptance of Interfaith Marriages Among Various Islamic Sects - Ilham Saputra; Melinda Oktaviani (Indonesian Journal of Islamic Law, 2021)
This research examines the acceptance of interfaith marriages among various Islamic sects, with a focus on Sunni, Shia, and others, in the context of maqā ṣ id ash-shari'ah . Using qualitative methodology, this research involved in-depth interviews and focus group discussions to collect data from ulama, community leaders, and individuals involved in interfaith marriages. Data analysis shows significant variation in acceptance of interfaith marriages between sects, which is influenced by religious education, interreligious interactions, and local policies. This research also explores how education and policy can be used as tools to increase interfaith dialogue and tolerance. The research results suggest that inclusive religious education and policies that support interfaith activities can strengthen tolerance and interfaith understanding in Muslim societies. These findings offer important insights for a better understanding of the complexities of interfaith marriages in the context of Islamic plurality and suggest strategies for increasing social coherence in diverse societies.